Qualitative study on domestic social robot adoption and associated security concerns among older adults in Slovenia - Žvanut, Boštjan; Mihelič, Anže (Frontiers in Psychology, 2024)
Introduction: Despite the increasing use of domestic social robots by older adults, there remains a significant knowledge gap regarding attitudes, concerns, and potential adoption behavior in this population. This study aims to categorize older adults into distinct technology adoption groups based on their attitudes towards domestic social robots and their behavior in using the existing technology. Methods: An exploratory qualitative research design was used, involving semi-structured interviews with 24 retired Slovenian older adults aged 65 years or older, conducted between 26 June and 14 September 2023. Results: Four distinct groups of older adults were identified: 1) Cautious Optimists, 2) Skeptical Traditionalists, 3) Positive Optimists, and 4) Technophiles based on eight characteristics. Discussion: These groups can be aligned with the categories of the Diffusion of Innovation Theory. Privacy and security concerns, influenced by varying levels of familiarity with the technology, pose barriers to adoption. Perceived utility and ease of use vary considerably between groups, highlighting the importance of taking into account the different older adults. The role of social influence in the adoption process is complex, with some groups being more receptive to external opinions, while others exhibit more autonomous decision-making.